Electrical properties and strain distribution of Ge suspended structures. (June 2015) - Shah, V.A.; Rhead, S.D.; Finch, J.; Myronov, M.; Reparaz, J.S.; Morris, R.J.; Wilson, N.R.; Kachkanov, V.; Dolbnya, I.P.; Halpin, J.E.; Patchett, D.; Allred, P.; et al.
Abstract: Germanium membranes and microstructures of 50–1000 nm thickness have been fabricated by a combination of epitaxial growth on a Si substrate and simple etching processes. The strain in these structures has been measured by high-resolution micro-X-ray diffraction and micro-Raman spectroscopy. The strain in these membranes is extremely isotropic and the surface is observed to be very smooth, with an RMS roughness below 2 nm. The process of membrane fabrication also serves to remove the misfit dislocation network that originally forms at the Si/Ge interface, with benefits for the mechanical, optical and electrical properties of the crystalline membranes.